Nepal Development Update : Investing in People to Close the Human Capital Gap - World Bank Group (World Bank, Washington, DC, 2019)
Gross domestic product (GDP) growth in Nepal is estimated at 7.1 percent in FY2019, driven mainly by the service and agriculture sectors. The service sector is likely to grow by 7.5 percent due to a boost in the retail, hotel, and restaurant subsectors, driven by an uptick in tourist arrivals and remittance-fueled private consumption. Agriculture is estimated to grow by 5 percent in FY2019, well above its 30-year average of 3.1 percent, due to good monsoons, increased commercialization, availability of fertilizers and seeds, and improved irrigation facilities. Industrial growth is also likely to be strong at 8.1 percent, well above its 30-year average of 5 percent, mainly due to improved power availability from increased electricity generation. Private investment and consumption are likely to be the main contributors to growth on the demand side. However, public investment is projected to contract due to a slowdown in post-earthquake reconstruction and delays in national pride projects like Melamchi water supply and Upper Tamakoshi hydroelectric.